The Representation of Female Masculinity in the Enola Holmes Mysteries - Syah Jehan Amrullah (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research analyzes female masculinity in Enola Holmes Mysteries. The term of female masculinity is represented in the novel through the main character, Enola because all the characteristics, behaviors and also her actions represent female masculinity. There are two goals of this research that conclude finding the representation of female masculinity in the novel and the critical position of the author. The theory used to analyze this research is from Stuart Hall’s theory of representation as the main theory supported by the five concepts of female masculinity that is propose by Halberstam (1998). The two theories are applied to analyze the representation of female masculinity through Enola Holmes Mysteries. To analyze this research, the first step is to select all the collected data using representation theory by Hall (1997). In this theory, there are 3 divided approaches, namely the reflective approach, the intentional approach, and the constructionist approach. Among these three approaches, the constructionist approach is the most suitable approach to be applied in this research. The constructionist approach is used to find the discourse contained in the novel. The discourse is used to find a representation of female masculinity through the main character in the novel. The five concepts of female masculinity that is proposed by Halberstam (1998) is used to this study to analyze female masculinity. There are two data categories in this study: primary data and secondary data. The primary data is a data obtained through novels in the form of dialogues and narrative. The secondary data is obtained from other sources in the form of interviews, article, journals and so on to support primary data as the information support. Through the data obtained in the novel, it can be concluded that the representation of female masculinity can be seen through the actions, behaviors, and Enola’s ideology in the novel and was dominated not only by the appearances, but mostly are her actions and ideology. Springer is trying to convey her goals through her work in The Enola Holmes Mysteries. As a strong feminist, Springer tries to encourage women that masculinity in females is normal and not exclusive to men; in some circumstances, masculinity can be owned by females without preaching or challenging ideology.
Reupload File Repositori 3 Februari 2026_Rudy K/Lia
Keywords: Female Masculinity; Enola Holmes Mysteries